The evaluation of shear deformation for contact analysis with large displacement - Nizam, Z. M.; Obiya, H.; Ijima, K.; Azhar, A. T. S.; Hazreek, Z. A. M.; Mohd Zin, Nur Shaylinda (IOP Publishing, 2018)
A common problem encountered in the study of contact problem is the failure to obtain stable and accurate convergence result when the contact node is close to the element edge, which is referred as "critical area". In previous studies, the modification of the element force equation to apply it to a node-element contact problem using the Euler-Bernoulli beam theory [1]. A simple single-element consists two edges and a contact point was used to simulate contact phenomenon of a plane frame. The modification was proven to be effective by the convergeability of the unbalanced force at the tip of element edge, which enabled the contact node to "pass-through", resulting in precise results. However, in another recent study, we discover that, if shear deformation based on Timoshenko beam theory is taken into consideration, a basic simply supported beam coordinate afforded a much simpler and more efficient technique for avoiding the divergence of the unbalanced force in the "critical area". Using our unique and robust Tangent Stiffness Method, the improved equation can be used to overcome any geometrically nonlinear analyses, including those involving extremely large displacements.